2023
DOI: 10.3390/fishes8050259
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Ginger Powder and Ginger Extract Nanoparticles: Effects on Growth, Immune–Antioxidant Status, Tissue Histoarchitecture, and Resistance to Aeromonas hydrophila and Pseudomonas putida Infection in Oreochromis niloticus

Abstract: A 10 week feeding trial was conducted to evaluate the potential effects of ginger powder (GP) and ginger extract nanoparticles (GNPs) on the growth parameters, digestive enzymes (lipase and amylase) activities, blood hematology, blood biochemical indices, immune indices (interleukin 10, immunoglobulin M, nitric oxide, and lysozymes), antioxidant activity, histological characteristics of kidney, spleen, liver, and intestine, and resistance to Aeromonas hydrophila or Pseudomonas putida infection in Nile tilapia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…[11][12][13][14] The supplementation of ginger extract in aquatic animal's diets has shown positive effects on growth performance in benni fish, Mesopotamichthys sharpeyi, 15 common carp, Cyprinus carpio, 14 black rockfish, Sebastes schlegelii, 16 and Nile tilapia, Oreochromis niloticus. 17 Although ginger is widely researched in fish species, to the best of our knowledge, few studies have reported the effects of its extracts on shrimp as a feed additive. [18][19][20] The objective of the present study was to investigate the effects of ginger extract on growth parameters, activity of digestive enzymes, and tolerance to high ammonia and low salinity conditions of the whiteleg shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The supplementation of ginger extract in aquatic animal's diets has shown positive effects on growth performance in benni fish, Mesopotamichthys sharpeyi, 15 common carp, Cyprinus carpio, 14 black rockfish, Sebastes schlegelii, 16 and Nile tilapia, Oreochromis niloticus. 17 Although ginger is widely researched in fish species, to the best of our knowledge, few studies have reported the effects of its extracts on shrimp as a feed additive. [18][19][20] The objective of the present study was to investigate the effects of ginger extract on growth parameters, activity of digestive enzymes, and tolerance to high ammonia and low salinity conditions of the whiteleg shrimp.…”
Section: Introductionmentioning
confidence: 99%